Infrastructure & Ops Superstream Series : CI/CD - Newman, Sam; Morris, Kief; Wilson, Christie; Schutta, Nathaniel; Deen, Jessica; Waterhouse, Heidi (O'Reilly Media, Inc., 2021)
The combination of modern distributed architectures and cloud environments offers powerful solutions for delivering applications that quickly yield business value. . .and increased complexity. Moving quickly and not breaking things means that you need deployment pipelines. How do you ensure your releases don't bring down production? Enter CI (continuous integration) and CD (continuous delivery), which greatly improve visibility of the quality of your software while also greatly reducing the time taken between releases. Join us to learn how CI/CD can help you achieve new levels of velocity, agility, reliability, and efficiency in your projects and systems. About the Infrastructure & Ops Superstream Series: This five-part series of half-day online events details what you need to know to effectively manage existing legacy systems while migrating to modern, scalable, cost-effective infrastructures-with no interruption to your business. Each event day covers some of the most challenging and promising topics facing those working in infrastructure and operations today: continuous integration and delivery, cloud delivery, Kubernetes, microservices, and security. What you'll learn-and how you can apply it Understand what tools work best for CI/CD and cloud native Learn how CI/CD works in the deployment pipeline Discover how infrastructure as code can help you deliver services to your users This Superstream is for you because ... You're a developer looking to discover the advantages of CI/CD. You want to better understand infrastructure as code. You work in a cloud native environment and want to learn which CI/CD tools work best with this extra complexity. You want to better incorporate testing and automation in your CI/CD pipeline. Prerequisites: Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read Infrastructure as Code, second edition (book) Read Building Microservices, second edition (book) Read What Is DevOps? (report).